Hyperactivity of Basal Ganglia in Patients With Parkinson's Disease During Internally Guided Voluntary Movements - Filyushkina, Veronika; Popov, Valentin; Medvednik, Rita; Ushakov, Vadim; Batalov, Artem; Tomskiy, Alexey; Pronin, Igor; Sedov, Alexey (Frontiers in Neurology, 2019)
The contribution of different brain areas to internally guided (IG) and externally triggered (ET) movements has been a topic of debate. It has been hypothesized that IG movements are performed mainly through the basal ganglia-thalamocortical loop while ET movements are through the cerebello-thalamocortical pathway. We hypothesized that basal ganglia activity would be modified in patients with Parkinson’s disease during IG movement as compared with normal subjects. We used functional MRI (fMRI) to investigate the differences between IG and ET motor tasks. Twenty healthy participants and twenty Parkinson’s disease patients (OFF-state) were asked to perform hand movements in response to sound stimuli (ET) and in advance of the stimuli (IG). We showed that ET movements evoked activation of a few large clusters in the contralateral motor areas: the sensorimotor and premotor cortex, supplementary motor area (SMA), insula, putamen, motor thalamus and ipsilateral cerebellum. IG movements additionally evoked activation of a large number of small clusters distributed in different brain areas including the parietal and frontal lobes. Comparison between the activity of Parkinson’s disease patients and healthy volunteers showed a few important differences. We observed that along with the activity of the posterior areas, activation of the anterior areas of putamen was observed during IG movements. We also found hyperactivity of the ventral thalamus for both movements. These results showed that IG movements in PD patients were made with the involvement of both sensorimotor and associative basal ganglia-thalamocortical loops.